2021
DOI: 10.33021/icfbe.v2i1.3567
|View full text |Cite
|
Sign up to set email alerts
|

Women empowerment through local wisdom as production differentiation strategy

Abstract: <p><em>This article explores the application of production differentiation strategy by women empowerment through local wisdom of Nasi Koco in the herritage area, Gajah Mada Street, Denpasar-Bali. The purpose of this article is to increase the sales of Nasi Koco by implementing new strategies to win the competition in similar businesses that have sprung up. The strategy that can be offered is a product differentiation, so that the product is more varied and not monotonous, that attracts consumer int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Case Study: "Nasi Koco" Production "Nasi Koco" production is included in the category of MSMEs, the name of a home-based business that produces packaged rice; this is one of the variants of Nasi Jinggo. Komalasari et al (2021a)…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Case Study: "Nasi Koco" Production "Nasi Koco" production is included in the category of MSMEs, the name of a home-based business that produces packaged rice; this is one of the variants of Nasi Jinggo. Komalasari et al (2021a)…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 99%
“…described Nasi Koco as "small in shape, wrapped in banana leaves, simple side dishes, and spicy tastethe hallmarks of Nasi Jinggo." Moreover, Komalasari et al (2021a) revealed that the product that has been given a unique name, "Nasi Koco," to distinguish it from the other variants of Nasi Jinggo, has a remarkable taste compared to most Nasi Jinggo.…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 99%
See 1 more Smart Citation